Pixels to principles: Reinforcing critical thinking skills in understanding environmental pollution using assemblr EDU digital visualization and anchored instruction learning model - Riyanto, Riyanto; Ummah, Roisatul; Saleh, Rahmat; Nisa, Khoirun; Iza, Nikmatul; Munawwaroh, Anita; Sunuyeko , Nurcholis (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2025)
This research comprehensively investigates the pedagogical effectiveness of integrating Augmented Reality (AR)-based digital visualization, facilitated by Assemblr EDU platform using Anchored Instruction (AI) learning model to improve students' critical thinking skills. The research method employed was a quasi-experimental research with a non-equivalent control group design, involving 60 seventh grade students (average age of 13-15 years old) from Global Islamic School Al Amin Junior High School Gondanglegi. The primary instrument for data collection was a valid and reliable critical thinking skills test (Cronbach's Alpha = 0.82), which was specifically designed to measure six crucial aspects of critical thinking. The experimental group adopted learning process that integrated an environmental pollution case study as an anchor by utilizing interactive AR model and visualization creation task using Assemblr EDU. In contrast, the control group was given a lesson using the same AI model but without the AR digital visualization component. The research findings portrayed a statistically significant difference (p < 0.05) in the improvement of critical thinking skills scores between the experimental group (mean gain score 19.7, SD = 3.1) and the control group (mean gain score 9.7, SD = 2.8). The Cohen's d effect size of 2.56 indicated a powerful impact of the intervention. This research provides important implications for science education practice, highlighting the transformative potential of visualization technology, particularly AR through easily accessible platforms such as Assemblr EDU, in enhancing student engagement, facilitating the understanding of complex concepts and empowering the development of their critical thinking skills in facing the increasingly complex environmental challenges